A preliminary analysis of post-pandemic employee motivation and retention among Filipino employees - Vivares-Beruin, Azel May; Beruin, Laurence Cruz (Indonesian Journal of Social Sciences, 2025)
In a post-pandemic competitive talent market, employee retention remains a pressing concern for businesses and organizations. This study examined the relationship between employee motivation and retention among Filipino employees across various industries. Data was collected from 114 respondents using a purposive sampling method and an online survey questionnaire. Descriptive statistics, correlation analysis, and regression analysis were employed to analyze the data. The correlation analysis revealed the following relationships: a weak positive relationship between physiological needs and employee retention, a moderately positive relationship between safety and security needs and employee retention, and strong positive relationships between affiliation needs, esteem needs, and self-actualization needs with employee retention. These findings highlight the significance of each category within Maslow’s needs theory as a motivator for employee retention. Regression analysis further revealed that, among the five categories, motivation tools related to affiliation needs are the most significant predictor of employee retention. The respondents also provided valuable insights into the main drivers of retention in their organizations, including salary as the primary factor, a comfortable work environment, medical benefits, training and development opportunities, promotion opportunities, and leave policies. These findings offer an important contribution to understanding how employee motivation influences retention in a post-pandemic workplace.